Development of a method for identification and accurate quantitation of aroma compounds in Chinese Daohuaxiang liquors based on SPME using a sol–gel fibre. (15th February 2015) - Wang, Pei-Pei; Li, Zhao; Qi, Ting-Ting; Li, Xiu-Juan; Pan, Si-Yi
Highlights: Volatile and aroma compositions of Chinese Daohuaxiang liquors were analysed. SPME coupled with GC–FID, GC–MS and GC–O was developed with a new fibre. The fibre had good sensitivity, high solvent stability and long lifetime. Wide linear ranges, low LODs, satisfactory precision and recoveries were achieved. Thirteen analytes were found to be the key aroma compounds of Daohuaxiang liquors. Abstract: Aroma compositions of Chinese Daohuaxiang liquors, including five kinds of commercial liquors and three kinds of base liquors, were extracted by solid phase microextraction using a sol–gel divinylbenzene/hydroxy-terminated silicone oil fibre. The effectiveness of the fibre was evaluated in comparison with commercial fibres and liquid–liquid extraction. After identification by GC–MS and GC–O, the compounds were accurately quantified by GC–FID using internal standards. Wide linear ranges, low limits of detection, satisfactory precision and recoveries were achieved. A total of 57 volatile compounds were detected and 28 of them were quantified. Most of them were common in these liquors but differed in terms of their relative amounts. Thirteen out of the 28 compounds had odour activity values greater than 1 in all of the liquors, and are suggested to be the key aroma-contributing substances of Daohuaxiang liquors. Besides, the differences among different aroma types and kinds of Daohuaxiang liquors were also discussed.